2019
DOI: 10.15640/jaes.v8n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability Effect on Food Crop Yield among the Smallholder Farmers in Lower Offin River Basin, Ghana

Abstract: The study assesses the effects of climate variability on food crop yield of the smallholder farmers in the Lower Offin River Basin, Ghana. Spline Interpolation and Spearman rank correlation coefficient were employed to examine the spatial and seasonal distribution of climate variables. Yield anomaly index and multiple linear regression models were used to assess the effect of climate variability on food crop yield. The results showed that the higher values of seasonality and replicability indices of rainfall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies have also shown that varying temperature fluctuations, heat waves, relative humidity, and rainfall are bound to compromise agricultural production as substantial losses are observed in the yield of grains such as rice, millet, sorghum, and maize in Nigeria (Sokoto et al 2016). It was similarly found that maize along with other cereals were more susceptible to climate variability with untold consequence on the yield (Bismark and Richard 2019). Similarly, it was found that yields and productivity of maize, millet, sorghum, and rice were negatively affected by unfavorable climatic conditions such as drought, excessive temperature, and low rainfall (Bamiro et al 2020).…”
Section: The Impact Of Climate Variability On Agriculture In Nigeriamentioning
confidence: 99%
“…Previous studies have also shown that varying temperature fluctuations, heat waves, relative humidity, and rainfall are bound to compromise agricultural production as substantial losses are observed in the yield of grains such as rice, millet, sorghum, and maize in Nigeria (Sokoto et al 2016). It was similarly found that maize along with other cereals were more susceptible to climate variability with untold consequence on the yield (Bismark and Richard 2019). Similarly, it was found that yields and productivity of maize, millet, sorghum, and rice were negatively affected by unfavorable climatic conditions such as drought, excessive temperature, and low rainfall (Bamiro et al 2020).…”
Section: The Impact Of Climate Variability On Agriculture In Nigeriamentioning
confidence: 99%